Gallbladder diaphragm: about a case - Marouane, Baiss; El Majdoubi, Hicham; Mohammed, Rabbani; Rahali, Anwar; Massrouri, Rahal; Said, Benamer; Lahlou, Khalid; Mdaghri, Jalil; Settaf, Abdellatif (International Surgery Journal, 2021)
Diaphragm gallbladder is a very rare anomaly of gallbladder embryogenesis. This malformation is very rare in adults and represents 0.1% of gallbladder anomalies. It can remain asymptomatic for a long time and be discovered fortuitously during a radiological examination for another pathology or be revealed by chronic abdominal pain or by a complication such as cholecystitis or biliary peritonitis. We report the observation of a 34 years old woman with chronic hepatic colic. The biological work-up including a blood count, a hepatic cytolysis and cholestas and CRP determination did not reveal any abnormality, whose morphological examinations concluded to an uncomplicated diaphragm gallbladder. A laparoscopic cholecystectomy was performed. The post-operative course was unremarkable. The intraoperative finding by opening the cholecystectomy specimen confirmed the diagnosis of a diaphragm gallbladder. Histological study confirms the diagnosis of diaphragm vesicle cholecystitis. In this document, we described the clinical and radiological characteristics of this rare anomaly.